Adverse childhood experiences, crime and health - Alves, Joana Ferreira Cardoso (2012)
Background: Incarcerated women have substantial health needs and histories of adverse childhood. Methods: As part of a study about the health of women prisoners, we pursued an exploration of the correlation between adverse childhood experiences, number of incarcerations, anxiety and depression symptoms, and health complains, in a sample of 195 incarcerated women. Participants filled out self-report questionnaires (life history, health complaints, anxiety and depression). Findings:The results show significant correlations between adversity and number of imprisonments (r = .198, p = .006), anxiety (r = .255, p = .000) and depressive symptoms (r = .320, p = .000), and health complains (r = .293, p = .000). Discussion: These results emphasize the association between adverse childhood experiences, delinquency and physical and mental symptoms in inmate women. We point out the importance of taking in consideration the adverse history in the layout of intervention towards this population in order to minimize consequences of early victimization.